Introduction to electronic commerce - Turban, Efraim; King, David; Lang, Judy (Upper Saddle River, NJ : Pearson/Prentice Hall, 2011)
Explore the essential concepts of electronic commerce. Written by experienced authors who share academic as well as real-world practices, this text features exceptionally comprehensive yet manageable coverage of a broad spectrum of EC essentials from a global point of view. The third edition pays special attention to the most recent developments in online behavior in our business, academic, and personal lives.
&#x000A
Overview of electronic commerce -- E-marketplaces : strictures and mechanisms -- Retailing in electronic commerce : products and services -- Online consumer behavior, market research, and advertising -- B2B E-commerce -- Innovative systems : from E-government and E-learning and C2C commerce -- The web 2.0 environment and social networks -- Mobile computing and commerce -- EC security and fraud protection -- Electronic payment systems, order fulfillment, and other services -- E-commerce strategy and implementation : globalization, SMEs, regulatory and ethical issues -- Launching a successful online business and EC projects.
Prev. ed. published under author: Efraim Turban.
Includes bibliographical references and index.
oif 21/05/14
Loan
Keywords: Electronic commerce